Advances in the device design and printing technology for eco-friendly organic photovoltaics. Issue 1 (15th December 2022) - Li, Haojie; Liu, Siqi; Wu, Xueting; Yao, Shengyi; Hu, Xiaotian; Chen, Yiwang
Abstract : This perspective systematically discusses strategies of optimization of active layer films in the preparation of organic photovoltaic (OPV) devices by green printing. Abstract : Green solvent-treated organic solar cells (OSCs) have demonstrated significant potential in terms of commercialization in recent years. However, the low solubility and high boiling point of green solvents cause difficulties in morphology exploration and tuning, and are eventually detrimental to photovoltaic properties. In this perspective, the recent research advances in green solvent-treated OSCs are summarized, and solvent selection strategies along with the associated optimization strategies in green printing of OSCs are discussed. Furthermore, the optimization strategies of OSCs fabricated using a large-area printing process are discussed in-depth to provide theoretical guidance for the large-scale fabrication of organic photovoltaic (OPV) modules.